1983
DOI: 10.1177/1077727x8301200204
|View full text |Cite
|
Sign up to set email alerts
|

Output‐Related Evaluations Of Unpaid Household Work: A Challenge for Time Use Studies

Abstract: This paper reviews monetary evaluations of unpaid household work, taking as a starting point the output of household productive activity. Possibilities for further developments are outlined, and desirable characteristics of such evaluations are advanced. A question is asked: Can time use research provide the necessary data? From an examination of data already collected in time use surveys, the reply appears to be in the affirmative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…The study was conservative in its approach and did not attempt to value unpaid domestic service since it is particularly difficult to establish wage rates for services (such as cooking and child care) which are not purchased in a traditional subsistence economy like that of Nepal. The recent work of Goldschmidt-Clermont [33], however, suggests that it may be possible to develop a similar output-related approach to valuing domestic service as well. 4.…”
Section: Potential Programme and Policy Relevancementioning
confidence: 99%
“…The study was conservative in its approach and did not attempt to value unpaid domestic service since it is particularly difficult to establish wage rates for services (such as cooking and child care) which are not purchased in a traditional subsistence economy like that of Nepal. The recent work of Goldschmidt-Clermont [33], however, suggests that it may be possible to develop a similar output-related approach to valuing domestic service as well. 4.…”
Section: Potential Programme and Policy Relevancementioning
confidence: 99%
“…Indeed, about 20 percent of the households included in the sample for this valuation (details of this sample are provided below) purchase childcare in the market, spending approximately £3,200 per annum (13 percent of these households' annual gross household incomes). 8 As highlighted above, criticism of input-based approaches has focused on differences in productivity between a worker in the market and a worker in the home (Goldschmidt-Clermont 1993a). In response to this criticism, it has been suggested that the market wage be adjusted to reflect differences in productivity between home and market production (Quah 1993;Abraham and Mackie 2005).…”
Section: Assigning Shadow Wagesmentioning
confidence: 95%
“…Historically, valuations using an input approach are more common (see Hawrylyshyn [1976]; Luisella Goldschmidt-Clermont [1983]; and International Research and Training Institute for the Advancement of Women [INSTRAW 1995] for extensive reviews of inputbased approaches). However, many researchers regard the output method as superior (Goldschmidt-Clermont 1983, Ronald Schettkat 1985John Fitzgerald and John Wicks 1990;Luisella Goldschmidt-Clermont 1993b). This viewpoint is very much in line with guidelines for market-based national accounts, which state that market prices for goods and services are the ''basic reference for valuation in the system'' (United Nations 1993: 2.68).…”
Section: Valuing Houshold Production: Inputs Versus Outputsmentioning
confidence: 96%
See 1 more Smart Citation
“…Advantages and disadvantages of these methods are discussed in Chadeau [4], Ferber and Birnbaum [7], Goldschmid-CIermont [12], Hawrylyshyn [14], Kinsey [18], Murphy [25,26] and Zick and Bryant [36,37]. The objective of this study is to estimate the value of homemaker's time in Canadian households using variant methods of the opportunity cost approach and to evaluate the relative limitations and merits of these various methods.…”
Section: Introductionmentioning
confidence: 99%